Mercury stable isotope composition of lichens and mosses from Northern Eurasia reveals Hg deposition pathways and sources - Sonke, Jeroen E.; Shevchenko, Vladimir P.; Prunier, Jonathan; Sun, Ruoyu; Prokushkin, Anatoly S.; Pokrovsky, Oleg S. (ACS earth and space chemistry)
Mercury (Hg) concentrations in lichens and mosses can be used as surrogates for atmospheric Hg deposition to continental surfaces. In this study, we collected and analyzed Hg concentrations (n = 334) and isotopic composition (n = 67) of epiphytic tree lichens and terricolous lichens and mosses from remote locations across the Eurasian Arctic and sub-Arctic (50 to 72 degrees N, 30 to 180 degrees E). The total Hg (THg) concentrations ranged from 13 to 7700 ng g-1. Epiphytic tree lichens had significantly higher median THg levels (243 ng g-1) than terricolous lichens (35 ng g-1) and mosses (74 ng g-1). THg is substantially higher in both tree lichens and terricolous lichens near the Arctic Ocean shore and up to 300 km inland. The combined delta 202Hg, Delta 199Hg, and Delta 200Hg signatures suggest that the elevated coastal Hg levels are delivered by marine air masses rich in gaseous and particulate-oxidized HgII forms, such as HgBr2. Similar to other vegetation Hg isotope studies, inland terricolous lichen and moss Delta 200Hg are near zero, indicating a dominant (63%) atmospheric Hg0 origin followed by HgII wet and dry deposition. Inland tree lichens carry a more positive Delta 200Hg of 0.15 parts per thousand, similar to the atmospheric HgII end-member, suggesting that they preferentially accumulate HgII wet and dry deposition compared to colocated terricolous lichens. Mosses from the European sub-Arctic show a low delta 202Hg of-3.1 parts per thousand, which we speculate to result from regional soil Hg0 emissions that are recaptured by mosses. Overall, the Hg isotope variability of mosses and lichens reveals latitudinal gradients in Hg deposition pathways and